The invisible pillars; mapping the challenges and sustainable solutions for Nigeria’s construction artisans - Chinelo A. Ozigbo; Francis O. Okeke; Emeka J. Mba; Ikechukwu W. Ozigbo; Peter I. Oforji; Paul C. Ogbuefi; Chinyelu D. F. Onyia; Benignus U. Ugwu; Stephanie C. Onyia; Echezonachukwu O. Okolo; Eugene E. Ogbodo (Discover Sustainability)
Abstract The Nigerian construction industry thrives on the labour of local artisans and despite their vital role, persistent challenges stifle their productivity and prudential value. This study aims to assess these obstacles by investigating the perceptions of these challenges by the local artisans in Enugu Metropolis, Nigeria. Through a structured survey of 466 artisans across 13 distinct muster points, this research identifies and analyse the predominant challenges, their impacts, and potential intervention strategies. The findings reveal that irregular or low income (23.1%), poor working conditions (19.2%), and lack of access to tools and equipment (17.4%) constitute the most significant barriers. Trade-specific analysis demonstrates that these challenges manifest differently across specialisations, with masons primarily concerned with working conditions while electricians prioritise training deficiencies. Statistical analysis indicates that these obstacles affect artisans similarly regardless of experience level or educational attainment, suggesting deeply embedded structural issues within the industry. The principal impacts of these challenges include financial instability (28%), decreased job satisfaction (24%), and reduced productivity (22%). Notably, 70% of respondents expressed willingness to participate in support programmes, identifying fair wages (20.6%), access to better tools (19.1%), and enhanced training opportunities (17.8%) as their preferred interventions. These findings align directly with Sustainable Development Goals 8 (Decent Work and Economic Growth), 9 (Industry, Innovation and Infrastructure), and 11 (Sustainable Cities and Communities) by identifying specific pathways for improving working conditions, enhancing productivity, and building capacity within the construction workforce. This research provides evidence-based insights to inform targeted policy development, training initiatives, and industry reforms aimed at integrating artisans more effectively into Nigeria's evolving construction landscape. The implications extend beyond immediate artisan welfare to encompass construction industry sustainability, urban development quality, and achievement of international development goals, positioning workforce development as a critical component of sustainable construction strategy in developing economies.